MEMBANGKITKAN OPTIMISME DI TENGAH RESESI EKONOMI AKIBAT PANDEMI COVID-19 MELALUI WEBINAR - Purwanto, Edi (Universitas Bunda Mulia, 2021)
The community service is motivated by concerns about Indonesia's economic conditions because of the pandemic which is directly felt by all levels of society. The purpose of community service through the delivery of material in the Webinar is to raise public optimism, especially Webinar participants during the economic recession due to the COVID-19 pandemic. The implementation method is through the delivery of Webinar material at the invitation of the Central Board of MUKI. The materials presented included: (1) the impact of the pandemic on the economic recession and its scope, (2) the actual conditions of business operations during the pandemic, (3) the actual conditions of the employment during the pandemic, (4) the positive attitude in dealing with the crisis, and (5) business opportunities, especially online businesses, during the pandemic. The result is that participants have understood that the economic recession is not only affecting Indonesia, but is globally. Participants have realized the need to build optimism during a crisis and see business opportunities, especially online businesses, to be able to survive in the midst of a crisis